A new species of Microgecko Nikolsky, 1907 (Squamata: Gekkonidae) from Pakistan - Masroor, Rafaqat; Khisroon, Muhammad; Khan, Muazzam Ali; Jablonski, Daniel (Zootaxa, 2020)
Members of the dwarf geckos of the genus Microgecko Nikolsky, 1907 are distributed from western Iran to northwestern India, with seven currently recognized species. Three taxa have been reported from Pakistan, M. depressus, M. persicus persicus and M. p. euphorbiacola. The former is the only endemic species restricted to Pakistan. Herein, we describe a new species, Microgecko tanishpaensis sp. nov., on the basis of four specimens collected from the remote area of the Toba Kakar Range in northwestern Balochistan. The type locality lies in an isolated valley in mountainous terrain known for the occurrence of other endemic reptile species, including geckos. Microgecko tanishpaensis sp. nov. is differentiated from the morphologically similar species M. depressus by possessing larger size, five scales bordering the nostril, internasals (supranasals) scales in contact with nostril, two large pairs of postmentals, higher numbers of interorbitals (27–30), scales around midbody (76–84), ventral scales from the postmental to vent (144–156) and scales along dorsal midline from axilla to groin (75–86). A morphological comparison of M. tanishpaensis sp. nov. with other species of the genus and an updated identification key for the genus Microgecko are presented.